Dark matter interacts with variable vacuum energy - Sánchez G., Iván (2014)
We investigate a spatially flat Friedmann-Robertson-Walker (FRW) scenario with two interacting components, dark matter and variable vacuum energy (VVE) densities, plus two decoupled components, one is a baryon term while the other behaves as a radiation component. We consider a linear interaction in the derivative dark component density. We apply the χ 2 method to the observational Hubble data for constraining the cosmological parameters and analyze the amount of dark energy in the radiation era for the model. It turns out that our model fulfills the severe bound of Ωx(z ' 1100) < 0.009 at 2σ level, so is consistent with the recent analysis that include cosmic microwave background anisotropy measurements from Planck survey, the future constraints achievable by Euclid and CMBPol experiments, reported for the behavior of the dark energy at early times, and fulfills the stringent bound Ωx(z ' 1010) < 0.04 at 2σ level in the big-bang nucleosynthesis epoch. We also examine the cosmic age problem at high redshift associated with the old quasar APM 08279+5255 and estimate the age of the universe today.